Subjectivité îlienne et cheminement : De Patrick Chamoiseau à Soeuf Elbadawi - Malela, Buata B. (Romanica Silesiana)
Our purpose is to study how the island is manifested in the relationship between the movement in space and identity in the Caribbean literary discourse. We took Chamoiseau for paradigmatic case of contemporary writer. Our idea is this: the question of the subject is a way to make a double social and literary attack in the intellectual universe. And subjectivity is only possible by a self‑inner journey to another. This approach remains partial in Elbadawi which itself is limited to the exploration of an ego that suffers. And the conditions of possibility of this approach are threefold and is measured in space possible. Key words: Chamoiseau, Elbadawi, comparative literature, Island, francophone literature